THE EFFECT OF INFORMATION ABOUT FEMALE ENTREPRENEUR TOWARDS GENDER STEREOTYPE IN ADOLESCENTS - Olivia Ariantje Josephine; Bianda Dina Wimbowo; Dimas Dear Pratama; Ditya Larasati; Intan Amalia (MANASA, 2017)
Stereotype is cognitive frameworks that contain knowledge and belief about certain social group and seen as characteristics from certain group. Gender stereotype is belief about psychological characteristics of man (masculinity) and woman (femininity). Because of that, problems about gender also happen in the world of entrepreneurship. Topic about female entrepreneur often neglected by society because it’s associated with masculine characteristics. Considering all of the above, this quasi-experiment research aimed to know the effects of information about female entrepreneurship towards stereotype gender in adolescents. This between-subject, pretest-posttest control group design used purposive sampling to collect the research participants. Participants’ characteristics are 32 adolescents between 15 to 18 years old. Randomization was used to divide participants into the experimental and control group, each consists of 16 participants. Data were collected through questionnaire of stereotype content model (SCM). Pretest analysis showed that there is no significant difference between experimental and control group (t = -2.036, p = .051, p > .05). After intervention was given, posttest analysis showed that there is significant difference between experimental and control group (t = 2.429, p = .021, p < .05). Therefore, it is concluded that information about female entrepreneur does influence gender stereotype in adolescents.